Impact of TiO2, ZnO, and Ag nanoparticles on anammox activity in enriched river Nile sediment cultures: unveiling differential effects and environmental implications - Mohamed A. Abd EL-Aziz; Ali M. Saeed; Mohamed K. Ibrahim; Wael S. El-Sayed (BMC Microbiology)
Abstract Background The increasing use of nanoparticles (NPs) necessitates investigation of their impact on wastewater treatment processes, particularly anammox, a critical biological nitrogen removal pathway. This study explored the effects of short-term exposure to TiO2, ZnO, and Ag-NPs on anammox activity in enriched cultures derived from River Nile sediments. Materials and methods Anammox bacteria were identified and enriched, with activity confirmed through 16S rRNA and hydrazine oxidoreductase (hzo) gene amplification and sequencing. Activity assays demonstrated efficient ammonium removal by the enriched culture. Subsequently, the impact of different sized and concentrated NPs on anammox activity was assessed. Results XRD analysis confirmed NP behavior within the microcosms: TiO2 transformed, ZnO partially dissolved, and Ag remained ionic. hzo gene expression served as a biomarker for anammox bacterial activity. Interestingly, 100 nm TiO2-NPs up-regulated hzo expression, potentially indicating a non-inhibitory transformed phase. Conversely, ZnO and Ag-NPs across all sizes and concentrations significantly down-regulated hzo expression, suggesting detrimental effects. Ag-NPs amended microcosms showed a significant reduction (79%) in hzo gene expression and a detrimental effect on bacterial populations. Overall, anammox activity mirrored hzo expression patterns, with TiO2 (21 and 25 nm, respectively) exhibiting the least inhibition, followed by ZnO and Ag-NPs. Conclusion This study highlights the differential effects of NPs on anammox, with the order of impact being Ag > ZnO > TiO2. These findings provide valuable insights into the potential environmental risks of NPs on anammox-mediated nitrogen cycling in freshwater ecosystems.